Role of Civil Society in Community Development of Nepal - Acharya, Umesh Pd. (Pragya Darshan प्रज्ञा दर्शन, 2023)
This study is based on the role of civil society in community development in Nepal. It is mainly prepared by using secondary sources. Data is obtained through articles/newspapers/clubs of the organization. The role of civil society in training and skill development, group formation and mobilization is assessed to be satisfactory. In the areas of health and hygiene, education, drinking water, transport and communication too, the role is likely to improve in the coming days. The relationship between groups and individuals in the community has appeared to be good. Most civil societies agree on good relationships between groups and individuals. The main problems of civil society are issues of the sustainability of their activities and political bias. Organizations depend on donor funds and activities as they propose; so there is duplication of programs and activities in the community. The activities are very short and do not have a fixed duration required by the community; it is due to the dependence of the donor for the fund. Civil society is the main subject and agent of community development. It knows the cultural, social, political and geographical situation. The process of social mobilization and mobilization of resources is the pioneering path of civil development. Group training and mobilization are found to be very good in the community. Therefore, this study shows a great need for civil society in community development. The function of civil society is very respectable. People want to expand their activities but the civil society cannot expand because of lack of funds. The ground of honor developed by civil societies in terms group formation, social mobilization, resource mobilization, and saving habits in groups is remarkable. Civil society (CS) in Nepal has played an important role in the economic and political transformation of the country over the past three decades. As Nepal changes into a three-tier federal government system, the environment in which civil society organizations (CSOs) operate is also changing.